(3GdJaGMI aj GdfMhs - (3GdfMGS , CMeO Hf eMeO Hf ESeGYjd GdeQGOj GdeUQj, CHh LYaQ,J (B338 (3g` s
(3ChdgG (B:s
((3HGH CbSGe GdYQHjI(B) (3CYde Cf GdYQHjI JfbSe Ydi KdGKI CbSGe(B: (3GSe haYd hMQa LGA deYfi, aGdGSe eG LGR Cf jchf aGYdkG Ch eaYhdkG s
(3BNQgG (B:s
(3Ch GdC HjV hGdHjVGA, heQQJ HeSGLOce hefGHQce hGddg CYde, Je GdeNJUQ HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3fSNI ajgG VHWs
(3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B208 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B82s
Keywords: (3GdfMhs